An Examination of the Attitudes of Modern Chinese Teachers Toward Their Work and Professional Development - WANG FENGYUAN , WANG FENGYUAN; DR. NIDHI AGARWAL , DR. NIDHI AGARWAL (International Journal of Multidisciplinary Research and Studies, 2024)
In-service teachers in Guangzhou public schools will be surveyed about their opinions on professional development opportunities. Before recently, the Chinese government had stringent controls over any and all training programs meant to advance an employee's career. Only in recent years has China started decentralizing education to its provinces and cities, but this shift has had a significant impact (Chinese Embassy of Nepal, 2012; Xiaojiong, 2012; MOE, 2000). This research is a valuable tool for architects, engineers, and other professionals involved in planning and designing new developments. It will also be helpful in gauging how faculty members feel about pursuing advanced degrees.